2000
DOI: 10.1007/s007020070053
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for an association between the Glu298Asp polymorphism of the NOS3 gene and Alzheimer's disease

Abstract: Recently a significant association of a missense mutation (Glu298Asp) of the endothelial nitric oxide synthase (NOS3) gene with late-onset Alzheimer's disease (LOAD) was reported. We tried to replicate this finding in a Japanese sample of 121 patients with LOAD, 51 with early-onset AD (EOAD), and 165 medical controls. However, the genotype and allelic distributions for the Glu298Asp polymorphism were similar for these three groups, suggesting that the Glu298Asp polymorphism of the NOS3 gene has no relevance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
1
10
1
Order By: Relevance
“…Our conclusion contradicts other previous works in small samples from Chinese (75 LOAD patients plus 68 controls) and Japanese populations (121 LOAD patients plus 165 controls) where a lack of association between the Glu298Asp polymorphism with Alzheimer's disease was found (Kunugi et al 2000;Wang et al 2004). False-negative effect caused by smaller sample size may provide a possible explanation for these confused results.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Our conclusion contradicts other previous works in small samples from Chinese (75 LOAD patients plus 68 controls) and Japanese populations (121 LOAD patients plus 165 controls) where a lack of association between the Glu298Asp polymorphism with Alzheimer's disease was found (Kunugi et al 2000;Wang et al 2004). False-negative effect caused by smaller sample size may provide a possible explanation for these confused results.…”
Section: Discussioncontrasting
confidence: 85%
“…Dahiyat et al (1999) first found a significant association of LOAD and homozygosity for the Glu allele and the Glu/ Glu genotype of NOS3 Glu298Asp polymorphism. The finding was confirmed by subsequent studies (Guidi et al 2005;Ntais and Polycarpou 2005;Akomolafe et al 2006), but others have failed to find a significant association (Singleton et al 2001;Kálmán et al 2003;Monastero et al 2003;Tedde et al 2002;Sánchez-Guerra et al 2001;Kunugi et al 2000;Wang et al 2004).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Other groups have analysed this polymorphism, but they did not find any significant association when studying US [2], Japanese [5,6] and UK populations [9]. In light of these conflicting results we analysed the segregation of the NOS 3 Glu298Asp and ApoE polymorphisms in 315 Italian subjects including 220 AD patients: 132 AD patients (48 males and 84 females; age ranging 49-96 years; age at onset 65.7 ± 8.6 mean ± SD) and 88 FAD patients [46 late-onset FAD (LOFAD) (age at onset 70.7 ± 4.2 years) and 42 early-onset FAD (EO-FAD) (age at onset, 56.7 ± 6.8 years)].…”
mentioning
confidence: 99%
“…Previous studies [2, 3, 5, 6, 9] world-wide have reported very different distributions of Glu/Glu genotype in different populations such as in US (AD=44.9 %; controls=50.8 %), [2], UK (EO-FAD=42.6 %, LOFAD=53-61 %; controls=39 %) [ [6] and (EOAD=87.8 %, LOAD=84.5 %; controls=84.9 %) [5]. The NOS 3 Glu/Glu genotype distribution in our control group and AD patients is similar to that of UK and US populations, while it is lower than in Japanese populations, thus suggesting that genetic heterogeneity in different ethnic groups may account for contrasting results in the distribution of this polymorphism.…”
mentioning
confidence: 99%